2016
DOI: 10.1097/shk.0000000000000548
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Mesenchymal Stem Cells Suppress Acute Lung Injury Induced by Lipopolysaccharide Through Inhibiting the TLR2, 4/NF-κB Pathway in Rats with Multiple Trauma

Abstract: Our results suggest that BMSCs suppress the inflammatory reactions through inhibition of the TLR2, 4 mediated NF-κB signal pathway, which hints that BMSCs can potentially be used to treat ALI in multiple trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…It is reported that numerous Chinese traditional medicines can protect against LPS-induced ALI via inhibiting TLR4/NF-κB signaling, which includes Lianqinjiedu (LQJD),36 Mogroside IIIE,37 Artesunate,38 and so on. Activation of NF-κB promotes the production of inflammatory cytokines mainly through the resynthesis of IκB,39,40 leading to diffuse alveolar damage in the lung 41. Similar to these reports, our data illustrated SU5416 could inhibit LPS-evoked injury to alveolar epithelial cells and area of inflammation infiltration in lung tissues.…”
Section: Discussionsupporting
confidence: 87%
“…It is reported that numerous Chinese traditional medicines can protect against LPS-induced ALI via inhibiting TLR4/NF-κB signaling, which includes Lianqinjiedu (LQJD),36 Mogroside IIIE,37 Artesunate,38 and so on. Activation of NF-κB promotes the production of inflammatory cytokines mainly through the resynthesis of IκB,39,40 leading to diffuse alveolar damage in the lung 41. Similar to these reports, our data illustrated SU5416 could inhibit LPS-evoked injury to alveolar epithelial cells and area of inflammation infiltration in lung tissues.…”
Section: Discussionsupporting
confidence: 87%
“…Excessive inflammation and pneumocyte apoptosis are the primary pathologies of ALI (26,27). MSCs are potent tools for improving these lesions (28).…”
Section: Discussionmentioning
confidence: 99%
“…MSCs are potent tools for improving these lesions (28). MSCs may exert preventive or inhibitory effects on the inflammatory response via TLR3-regualted mitogen-activated protein kinase and TLR2/4-NF-κB signaling pathway in LPS-induced lung injury (26,29). MSCs have been suggested to possess additional functions for the treatment of ALI/ARDS, including homing to inflammatory sites, differentiating into pneumocytes, secreting multiple soluble factors that may repair injured pneumocytes and performing immunomodulatory effects (8,30,31).…”
Section: Discussionmentioning
confidence: 99%
“…This idea is supported by different studies conducted in pathological conditions demonstrating that MSCs, exposed to damage associated molecular pattern (DAMP) or pathogen-associated molecular pattern (PAMP), could react by reverting the production of pro-inflammatory to anti-inflammatory molecules [23, 24] and by inducing the switch from pro-inflammatory M1 macrophages maturation to the anti-inflammatory M2 phenotype [25]. These observations open the field to the hypothesis that an enhancement of MSCs potential would benefit the progress of many orthopedic conditions.…”
Section: Mesenchymal Stem Cells: a Multimodal Tool To Treat Musculoskmentioning
confidence: 94%